Impact of psychiatric pharmacist-led ambulatory alcohol withdrawal management - Maxwell Lamb, PharmD, BCPS; Michelle Colvard, PharmD, BCPP; Jonathan Lister, PharmD, BCPP; Eric Johnson, PharmD, BCPP (Mental Health Clinician)
Introduction Alcohol withdrawal syndrome (AWS) is a complication of alcohol use disorder commonly encountered across various healthcare settings. Management of AWS is routinely conducted in the inpatient setting; however, in numerous patients, ambulatory alcohol withdrawal management (AAWM) is safe, effective, and recommended. There is no published evidence describing psychiatric pharmacists, otherwise known as Psychiatric Clinical Pharmacist Practitioners (psychiatric-CPP) impact on AAWM. Methods This was a single-centered, retrospective review conducted at a Veterans Affairs Healthcare System that aimed to quantify and describe the clinical impact of psychiatric-CPP–led AAWM. Veterans who participated in AAWM with a psychiatric-CPP from April 1, 2019, to December 31, 2023, were included in the study. Descriptive statistics were used. Results The rate of successful AAWM was 67.6% (n = 23) for 34 total withdrawal episodes. The most common reason for failure was breakthrough withdrawal or cravings at 45.5% (n = 5). The most common medications utilized included gabapentin (62.9%; n = 22), chlordiazepoxide (8.6%; n = 3), and diazepam (8.6%; n = 3). In 3 AAWM episodes, no medications were used. Cost avoidance of outpatient management rather than inpatient management was calculated to be $139,361.24. There were 2 alcohol-related emergency department visits within the first month of psychiatric-CPP–conducted AAWM, and no serious medical complications were noted. Discussion Psychiatric-CPPs practicing in a Veterans Affairs Healthcare System successfully completed AAWM in a majority of the episodes that were attempted. Additionally, few patients were seen in an emergency department setting for alcohol-related matters after initiation of AAWM, perhaps emphasizing the safety of this service and the need for further use.